Antibiotic resistance gene typing in Staphylococcus aureus isolated from bovine mastitis - MUSHTAQ, MOHSINA; AGRAWAL, RAJESH; BHAT, MOHD. ALTAF; SINGH, RAJIV; PANDE, NISHI (The Indian Journal of Animal Sciences, 2019)
The study was conducted to determine the antimicrobial resistance pattern of Staphylococcus aureus isolates from bovine mastitis. Milk samples (160) collected aseptically from mastitis affected cows at organized dairy farms in and around Jammu were subjected to microbial culture for the isolation and identification of S. aureus using Baird Parker Agar. Presumptive S. aureus isolates (52) were subjected to molecular confirmation through identification of species specific (nuc) gene. In vitro antimicrobial resistance pattern of the isolates against a panel of 13 selected antibiotics, using disc diffusion technique, revealed that the isolates were mostly sensitive to enrofloxacin followed by vancomycin, ciprofloxacin, tetracycline, chloramphenicol, streptomycin, ceftriaxone, erythromycin and gentamicin whereas maximum resistance was shown towards penicillin G followed by ampicillin, amoxyclav, methicillin, gentamicin, streptomycin, erythromycin, tetracycline and ceftriaxone. Methicillin resistance (MRSA) was recorded in 32.69% S. aureus isolates out of which 41.17% isolates carried mecA gene. Among the gentamicin and tetracycline resistant S. aureus isolates, 61.53% isolates carried aacA-aphD gene and 80% isolates carried tetK gene, respectively. Multidrug resistance (MDR) was observed in 71.15% S. aureus and 82.35% MRSA isolates. In conclusion, S. aureus showed maximum sensitivity to enrofloxacin thereby suggesting the use of this drug for effective treatment of mastitis but the development of resistance against this drug cannot be ruled out in the near future, hence, there is a need for accurate diagnosis of mastitis along with the correct selection of antibiotics to prevent bovine mastitis.